Surgical outcome of benign cases with pelvic adhesions undergoing robotic total hysterectomy. Issue 8 (6th June 2022) - Wang, Pei-Yi; Lee, Yu-Chieh; Liu, Wei-Min; Chen, Ching-Hui
Abstract : Background: Robotic total hysterectomies have been considered contraindicated for patients with intra-abdominal adherences, but the evidence for this is not strong, and we hypothesized that the procedure can be of benefit even in these cases. In our research, we analyzed how the severity of pelvic adhesions affects robotic total hysterectomy, and by comparing different types of adhesions, we can further identify the outcomes differences in between, which may aid in future surgical decision making. Methods: Prospective cohort study (Canadian Task Force classification II-2). All 410 patients with uterine myoma or adenomyosis undergoing robotic total hysterectomies between 2011 and 2016 using the da Vinci Si system by the same surgeon in Taipei Medical University Hospital were included in the study. Results: Baseline characteristics, blood loss, docking time, operation time, time to perform uterine artery ligation (UAL), pain score, hospital stay, complication rate, and laparotomy conversion rate were analyzed between benign cases with or without pelvic adhesions undergoing robotic total hysterectomy. Furthermore, in our subgroups analysis, we have divided the patients with adhesion into different groups according to the severity of adhesion. The abdomen and pelvic cavity was divided into nine sections, and the outcomes of different adhesion condition were compared. We found that patients with adhesions had increased docking time and operation time, but other differences between groups were not statistically significant. The results of the adhesion group showed no significant increases in blood loss, intra- and postoperative complications, and length of hospital stay. Only significantly longer surgical time compared with the normal group was noted. Conclusion: Our results suggest that robotic total hysterectomies with UAL are effective and safe for patients with benign gynecologic conditions, and the surgical method should be considered even for patients with adhesion risks.